Influenza A Virus PA Antagonizes Interferon-β by Interacting with Interferon Regulatory Factor 3 - Yi, Chenyang; Zhao, Zongzheng; Wang, Shengyu; Sun, Xin; Zhang, Dan; Sun, Xiaomei; Zhang, Anding; Jin, Meilin (Frontiers in Immunology, 2017)
The influenza A virus (IAV) can be recognized by retinoic acid-inducible gene I (RIG-I) to activate the type I interferon response and induce antiviral effects. The virus has evolved several strategies to evade the innate immune response, including non-structural protein 1 (NS1) and its polymerase subunits. The mechanism by which NS1 inhibits Interferon-β (IFN-β) is well understood, whereas the mechanism by which polymerase acid protein (PA) inhibits IFN-β remains to be elucidated. In this study, we observed that the IAV PA protein could inhibit the production of IFN-β and interferon-stimulated genes induced by Sendai virus (SEV) through interferon regulatory factor 3 (IRF3), but not through nuclear factor-kappaB (NF-kappaB). Additionally, PA inhibited IFN-β induction by RIG-I, melanoma differentiation-associated gene 5 (MDA-5), mitochondria antiviral signaling protein (MAVS), TANK-binding kinase 1 (TBK-1), inhibitor of nuclear factor kappa-B kinase-ε (IKKε) and IRF3 overexpression. Furthermore, PA interacted with IRF3 to block its activation. The N-terminal endonuclease activity of PA was responsible for its interaction with IRF3 and inhibition of the IFN-β signaling pathway. In summary, our data reveal the mechanism by which IAV PA inhibits the IFN-β signaling pathway, providing a new mechanism by which the virus antagonizes the antiviral signaling pathway.